PERBEDAAN KEMANDIRIAN ANAK YANG SEBELUMNYA MENGIKUTI PLAY GROUP DAN TIDAK MENGIKUTI PLAY GROUP di TK Desa Sumbang Timun Kecamatan Trucuk Kabupaten Bojonegoro tahun 2014 Differences inchildren aged 4-5 years of independence that previously followed the - UTAMI, WIWIK; S, ATIK (Jurnal Penelitian Kesehatan, 2016)
The phenomenon that occurs in some students in the village Sumbang TimunÂ  there are Â students still ask accompanied in the classroom when learning activities and play in the classroom, then there is also the task of the teacher handed to his parents while learning and playing in class, aim study analyzes differences that previously followed the childs independence play group with kids who do not follow the play group in the village of Sumbang Timun. Analytical research design types comparative study with retrospective approach, with a population of 50 respondents. Large samples are 44 respondents, independentn variables is independence, dependentnya variable is children aged 4-5 years who had previously followed the play group and children aged 4-5 years who had not followed the play group sampling using random sampling techniques, data collected by observation later in editing, coding, scoring, tabulating, which is then analyzed with cross tabs. The results of the 44 respondents in Sumbang Timun are children who previously followed the play independent group of 20 children (90.9%), not independent as much as 2 children (9.1%), while that does not follow the play as an independent group of 8 children (18, 18%) and not independent 14 children (31.81%) There are differences in the independence of children aged 4-5 years earlier following the play group and who do not follow the play group, which previously follow play group is more independent than those not following the play group in the village of Sumbang Timun, and parents should be expected to involve the child in school play group before entering kindergarten to establish the independence of children from an early age.